2008
DOI: 10.1021/bi800180g
|View full text |Cite
|
Sign up to set email alerts
|

A Common Catalytic Mechanism for Proteins of the HutI Family

Abstract: Imidazolonepropionase (HutI) (imidazolone-5-propanote hydrolase, EC 3.5.2.7) is a member of the amidohydrolase superfamily and catalyzes the conversion of imidazolone-5-propanoate to N-formimino-L-glutamate in the histidine degradation pathway. We have determined the three-dimensional crystal structures of HutI from Agrobacterium tumefaciens (At-HutI) and an environmental sample from the Sargasso Sea Ocean Going Survey (Es-HutI) bound to the product [ N-formimino-L-glutamate (NIG)] and an inhibitor [3-(2,5-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Early kinetic studies used IP produced in situ from urocanate in the presence of highly purified urocanase. As a result, the characterization of IPase lagged behind that of the other Hut enzymes, and IPase was the last of the enzymes to have its crystal structure determined (161,170). Although the details of the reaction mechanism and the nature of the active site metal remain somewhat unclear, two facts are well established: the reaction is essential for utilization of histidine as a carbon source (74,148), and IPase is a hydrolase that cleaves the ring to yield formiminoglutamate, in a different reaction from the nonenzymatic cleavage that yields formylisoglutamine (128).…”
Section: Ipasementioning
confidence: 99%
“…Early kinetic studies used IP produced in situ from urocanate in the presence of highly purified urocanase. As a result, the characterization of IPase lagged behind that of the other Hut enzymes, and IPase was the last of the enzymes to have its crystal structure determined (161,170). Although the details of the reaction mechanism and the nature of the active site metal remain somewhat unclear, two facts are well established: the reaction is essential for utilization of histidine as a carbon source (74,148), and IPase is a hydrolase that cleaves the ring to yield formiminoglutamate, in a different reaction from the nonenzymatic cleavage that yields formylisoglutamine (128).…”
Section: Ipasementioning
confidence: 99%
“…The reverse reaction, an intramolecular condensation, is reminiscent of the assumed formation of pseudochelin A. While sequence alignments of MxcM with different HutI homologs did not indicate significant similarities (see Table S1 in the supplemental material), a manual inspection showed that the active site residues of HutI (26,27) are conserved in MxcM (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…About 1 mg of pure protein was obtained from 15 g of cells. Cc2672 was expressed and purified to homogeneity as previously described (21). …”
Section: Methodsmentioning
confidence: 99%